Using difference in intersectional research with im/migrant and racialized sex workers - Ham, Julie (Theoretical criminology, 2020)
Intersectionality attends to the interactions between social difference and power, although theoretical models vary in their emphasis on one or the other. Difference-centred models often distinguish between processes of constructing social difference, systems that institutionalize social difference and identities that include social difference. This article discusses the analytical expectations that can emerge in intersectional research that focus on difference, by analysing the use and construction of difference by im/migrant and racialized women in sex work. The first analytical expectation is the distinction between salience and difference when starting from the lived realities and voices of individuals, groups and communities. The second analytical expectation concerns the interaction between two intersectional methodologies, between identities and lived experiences, and processes of constructing difference.